Hubungan antara Kepercayaan Epistemologi dan Pendekatan Belajar: Studi Metaanalisis - Ghufron, M. Nur (Faculty of Psychology, Universitas Gadjah Mada, 2009)
This study was a metaanalysis of the relationship between epistemological belief and approach learning. The quantitative review involved 52 studies from 11 articles that contained a combined sample of approximately 26818. This analysis extends previous works by directly correcting both sampling and measurements errors. The results provided support that one’s epistemological belief has a correlation with one’s learning approach. Thus epistemological beliefs serve as predictors learning approach